Models for soil conservation planning based on soil erosion and deposition rates - THAKUR, ARADHANA; ., POONAM; NEMA, A. K. (Journal of Soil and Water Conservation, 2018)
An increasing awareness by scientists, governments and the general public realized that Soil Erosion and sedimentation are the major environmental and agricultural problem in the whole world. It draws attention and led to the development of many useful models for the estimation of soil erosion and deposition rates. Models help to represent and simulate the actual hydrological processes so that areas most prone to severe damage and in need of greater soil and water conservation measures can be prioritized. Most of the models use remote sensing and GIS technique for estimation. This is the key step to better target finite resources for enhanced soil conservation measures.